Predicting writing performance outcome via writing self-efficacy and implication on L2 tertiary learners in Malaysia - Jalaluddin, Ilyana (IDOSI Publications, 2013)
Generally, this study looks into the connection between writing self-efficacy level and writing skills performance. It will look into detail the accuracy of how far writing self-efficacy able to predict the outcome of a learner in L2 context and the implication that it has on the learning of writing among L2 tertiary learners in Malaysia. This study had been conducted in one of Malaysian universities, Universiti Putra Malaysia and the participants were the final year undergraduate learners majoring in Applied Linguistics and Literature. An analysis was conducted by looking at two categories of writer namely high self-efficacy writer and low self-efficacy writer. Self-efficacy level was measured through Writing self-efficacy questionnaire. All of these writers’ essays had been collected and analysed qualitatively (i.e. language and content development) and quantitatively (i.e. scores) in order to relate to their writing self-efficacy level. Correlation analysis showed weak relationship between self-efficacy and writing skills performances. Apart from that, qualitative data depict two distinct style of writing between high self-efficacy writer and low self-efficacy writer and scores show that low self-efficacy writer performed better than high self-efficacy writer. The implications are discussed in relation to teaching and learning within the Malaysian tertiary setting.